Information Technology and Sustainability: Evidence from an Emerging Economy. Issue 4 (14th January 2018) - Khuntia, Jiban; Saldanha, Terence J. V.; Mithas, Sunil; Sambamurthy, V.
Abstract : Research in operations management and information systems suggests that information technology (IT) can play an important role in managing operations that support environmentally sustainable (green) growth. Yet, few studies have empirically assessed the efficacy of green IT investments and initiatives, particularly in emerging economies such as India. This study examines the performance consequences of green IT investment and implementation in terms of energy conservation and profit impact. We analyze an archival dataset constructed from a survey of nearly 300 organizations in India, matched partially with objective data from a secondary source. We find that green IT investment is positively associated with a higher profit impact and that this association is partially mediated by a reduction in IT equipment energy consumption. In addition, we find that operations‐oriented green IT implementation is positively associated with both IT equipment energy consumption reduction and profit impact, whereas supplier‐oriented green IT implementation is positively associated only with reduction in IT equipment energy consumption. Our findings are robust to objective measures of firm‐level total income and profit after tax. We highlight opportunities for further research and discuss the implications of the study for managerial practice to encourage the implementation of green IT initiatives that promote greater environmental sustainability.